GE_GERICHTE P/14752/2024 vom 31. Oktober 2025 - GE Cour de justice (2025)
IN DUBIO PRO REO;AVEU;SÉJOUR ILLÉGAL;INTERDICTION DE PÉNÉTRER DANS UNE ZONE;DIRECTIVE 2008/115/CE | LEI.115.al1.letb; LEI.119.al1